Latest performance results from the FONT5 intra-train position and angle feedback system at ATF2 - Christian, G; Apsimon, R; Bett, DR; Burrows, P; Davis, MR; Gerbershagen, A; Perry, C; Constance, B; Resta-Lopez, J (2011)
A prototype Interaction Point beam-based feedback system for future electron-positron colliders, such as the International Linear Collider, has been designed and tested on the extraction line of the KEK Accelerator Test Facility (ATF). The FONT5 intra-train feedback system aims to stabilise the beam orbit by correcting both the position and angle jitter in the vertical plane on bunch-to-bunch timescales, providing micron-level stability at the entrance to the ATF2 final-focus system. The system comprises three stripline beam position monitors (BPMs) and two stripline kickers, custom low-latency analogue front-end BPM processors, a custom FPGA-based digital processing board with fast ADCs, and custom kicker-drive amplifiers. An overview of the hardware, and the latest results from beam tests at ATF2, will be presented. A total systemlatency as low as approximately 140 ns has been demonstrated. Copyright © 2011 by IPAC'11/EPS-AG.